Reproductive Health is pleased to announce a mandatory open data policy in the journal - Salaria, Natasha (2016)
The field of global health is evolving and moving forward from not just securing open access publication toaid in the dissemination of research but further still,making the data underpinning the results of that publication open. Funders1 in the field, and recently theInternational Committee of Medical Journal Editors(ICMJE) [1], are increasingly requiring that researchersmake data produced during their grants publiclyaccessible.Although the push for more data sharing and transparency started with the genomics community, it is quicklyspreading to the global health communities. Indeed, twomajor organisations in the field have already set up a stronginfrastructure for data reuse and sharing. Many of us arealready familiar with the power of open data through theWHO Global Health Observatory Data Repository [2] andthe World Bank Open Data Catalogue [3], both of whichare invaluable resources. In February 2016 the WellcomeTrust also joined ?over 30 global health bodies in calling forall research data gathered during the Zika virus outbreak,and future public health emergencies, to be made availableas rapidly and openly as possible? [4]. This follows a consensus statement arising from a WHO consultation in September 2015 moving towards making this the global norm [5].Reproductive Health wants to help spearhead thisparadigm shift to ensure all data underlying the researchpublished within the journal is publicly available to ensure transparency of research and contribute to enhancing research in the field.